PENGARUH PENGGUNAAN TERAK SEBAGAI PENGGANTI AGREGAT KASAR TERHADAP KUAT LENTUR DAN BERAT JENIS BETON NORMAL DENGAN METODE MIX DESIGN - Susilowati, Dewi; Saputro, Ida Nugroho; Nurhidayati, Aryanti (Pendidikan Teknik Bangunan, 2013)
ABSTRACTDewi Susilowati. Research paper, Faculty of Teaching Training And Education Sebelas Maret University, Oktober 2013Concrete pavement is a mixture of cement, water, fine aggregate (sand), coarse aggregate (gravel). The use of concrete as a building material that increases in field will trigger the alternative materials are used as a substitute for gravel in making of concrete mixed. The use of slag that looks like crushed stone are expected as a substitute for gravel. The purpose of this research is to know the effect of slag as subtitution coarse aggregate for flexural strength and density of the normal concrete.The method used in this research is the experimental in the laboratory. Specimens used are shaped beam with a size of 15 cm x 15 cm x 60 cm . This test using slag as a coarse aggregate replacement with variation 0%, 20%, 40%, 60%, 80% and 100%. Number of specimens were made for each variation of slag replacement are 6 pieces for a total 36 pieces of the tested specimen. Tests were applied in the object is flexural strength tested with using a two- point loading at 1/3L distance and density of normal concrete tested.The results of the research showed variations replacement of slag coarse aggregate concrete cause flexural strength decreased as well as the density of normal concrete obtained on the variation of 80% slag replacement. At 100% slag replacement didn?t produce normal concrete because the resulting speciments density more than 2500 kg/m3.Keywords : slag, flexural strength, density, concrete